Effects of the implementation of second-line prenatal cell-free DNA testing on termination of pregnancy in a French perinatal network. (December 2021) - Duvillier, Clémence; Dard, Rodolphe; Hervé, Bérénice; Cohen, Camille; Vialard, François; Quibel, Thibaud
Abstract: Objective: To evaluate the impact of implementing cell-free DNA (cfDNA) testing on gestational age (GA) at termination of pregnancy in a French perinatal network. Methods: We conducted a retrospective study. All women having undergone a termination of pregnancy between 1 January 2012 and 31 December 2017 were included. We compared the periods before and after the introduction of second-line cfDNA testing, which started on 1 January 2015. Throughout the study period, the invasive procedures were foetal karyotyping and chromosomal microarray analysis. The primary study outcome was GA at termination. The secondary outcomes were GA at termination for trisomy 21 and the frequency and GA at the time of invasive procedures. Results: During the 6-year study period, 840 women underwent termination. The median GA at termination before and after the implementation of cfDNA testing was 19.4 and 19.0 weeks, respectively (p = 0.38). Although the frequency of termination for trisomy 21 increased significantly from 23% to 32% (p < 0.01), the median GA at termination did not change significantly (p = 0.80). The implementation of cfDNA testing was associated with a decrease in the frequency of invasive procedures in general and chorionic villus sampling in particular (p = 0.04). Conclusion: The introduction of cfDNA testing does not increase the GA at termination for trisomy21.